2020
DOI: 10.1186/s13049-020-00777-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated admission lactate levels in the emergency department are associated with increased 30-day mortality in non-trauma critically ill patients

Abstract: Background Elevated blood lactate levels were reported as useful predictors of clinical outcome and mortality in critically ill patients. To identify higher-risk patients, this investigation evaluated the relationship between patient mortality and admission lactate levels during the management of non-trauma critically ill patients in the emergency department (ED). Methods In this prospective, single centre observational study in a German university ED, all adult patients who were admitted to the ED resuscita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
2
13
0
4
Order By: Relevance
“…31 The thresholds used in our study (pH <7.00 and lactate ≥10.0 mmol/L) are representative of severe injury and in line with prior studies. [10][11][12] We acknowledge that the decision to stop transfusing blood is multifactorial in nature and certainly should not be based on laboratory values alone. Patient characteristics, comorbidities, and the nature of the disease process itself should all be taken into consideration, as multiple studies have demonstrated that these factors not only influence the efficacy of RBC transfusion, 32,33 but also impact clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…31 The thresholds used in our study (pH <7.00 and lactate ≥10.0 mmol/L) are representative of severe injury and in line with prior studies. [10][11][12] We acknowledge that the decision to stop transfusing blood is multifactorial in nature and certainly should not be based on laboratory values alone. Patient characteristics, comorbidities, and the nature of the disease process itself should all be taken into consideration, as multiple studies have demonstrated that these factors not only influence the efficacy of RBC transfusion, 32,33 but also impact clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Peak lactate was stratified into the following categories: 0.0–4.9, 5.0–9.9, and ≥10.0 mmol/L, while nadir pH was stratified into the following categories: <7.00, 7.00–7.19, 7.20–7.39, and ≥7.40. The peak lactate threshold of 10.0 mmol/L and the nadir pH threshold of 7.00 were chosen based on prior studies in critically ill and trauma surgery patients 10,12 . Patients were also categorized according to age (18–39, 40–64, and ≥65 years) and total RBC transfusion volume (30–39 RBC units, 40–49 RBC units, and ≥50 RBC units) to assess additional clinical variables that could potentially be used as markers of futility in massive transfusions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are a series of early warning scores based on different physiological parameters, which are capable of predicting the risk of deterioration in EDs [ 2 , 3 ], there are still situations in which SAEs could be detected earlier if there was an effective early warning [ 4 ].…”
Section: Introductionmentioning
confidence: 99%